THE ROLE OF THE BUKHARA SCHOOL OF FIQH IN ISLAM (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article, based on scientific analysis, illuminates the role of the fiqh school formed in the territory of Mawarannahr, particularly in Bukhara, in the development of Islam. The Bukhara school of jurisprudence became one of the centers of Hanafism in the 9th-12th centuries and had a significant influence on the development of not only regional but also general Islamic legal norms. The scientific heritage of such great jurists as Abu Hafs al-Kabir, Abu Hafs as-Saghir, Burhaniddin al-Marginani played an important role in the formation of the legal culture of the region. The article comprehensively analyzes the stages of formation of the Bukhara school of fiqh, its scientific principles, legal and methodological heritage, the system of madrasas, its socio-political influence, and its significance in Islam.